Prophylactic Fresh Frozen Plasma Infusion is Ineffective in Reversing Warfarin Anticoagulation and Preventing Delayed Intracranial Hemorrhage After Falls. (October 2015) - Reddy, Subhash; Sharma, Rohit; Grotts, Jonathan; Ferrigno, Lisa; Kaminski, Stephen
Background: Elderly patients, with considerable fall risk, are increasingly anticoagulated to prevent thromboembolic disease. We hypothesized that a policy of prophylactic fresh frozen plasma (FFP) infusion in patients having falls would reverse vitamin K antagonists (VKAs) and that reversal would decrease delayed intracranial hemorrhage (ICH). Methods: A retrospective review of patients with trauma admitted to a level 2 community trauma center was performed from January 2010 until November 2012. Inclusion criteria were: ground level fall (GLF) with suspected head trauma, on VKA, an international normalized ratio (INR) of >1.5, and a negative head computed tomography (CT). Patients were transfused with FFP to a goal INR of <1.5 while observed. Patients were classified as reversed (REV) if the lowest INR achieved within 4 to 24 hours after initial INR was <1.5 or unreversed (NREV) if lowest INR achieved was >1.5. Chi-square and logistic regression were performed. Results: A total of 194 patients met the criteria. In all, 43 (22%) patients were able to be REV, and 151 (78%) patients remained NREV. Unreversed patients were male and younger ( P < .05). There was no difference in mean FFP received. Unreversed patients had a higher initial INR of 3.0 compared to REV patients (2.5; P = .018). One patient developed a delayed ICH and belonged to the REV group. Conclusion: The incidence of delayed hemorrhage was 0.5%. A strategy of prophylactic FFP infusion was ineffective in VKA reversal. We recommend against prophylactic infusion of FFP during a period of observation for patients on VKA with suspected head trauma and a negative initial CT.